PERAN INVESTASI DALAM MEMODERASI PENGARUH PENDUDUK BEKERJA, IPM, UPAH MINIMUM TERHADAP PERTUMBUHAN EKONOMI KABUPATEN/KOTA PROVINSI BALI - Ni Made Ira Vary Ayesti; Gede Crisna Wijaya (Berajah Journal, 2026)
Economic growth is one of the main indicators used to measure the success of regional economic development. This study aims to analyze the role of investment in moderating the effects of the employed population, Human Development Index (HDI), and minimum wage on economic growth across regencies and municipalities in Bali Province. The analysis employed a quantitative approach using secondary panel data covering the 2019–2025 period. The analytical methods used were the Fixed Effect Model (FEM) and Moderated Regression Analysis (MRA). The results indicate that, simultaneously, the employed population, HDI, minimum wage, and investment have a significant effect on economic growth. Partially, HDI and investment have a positive and significant effect on economic growth, while the minimum wage does not have a positive and significant effect, and the employed population has no significant effect on economic growth. The moderation test results show that investment is unable to moderate the effects of the employed population, HDI, and minimum wage on economic growth in the regencies and municipalities of Bali Province. These findings suggest that improving the quality of human resources and strengthening investment remain essential to support sustainable economic growth in Bali Province.